Applying pyrolysis-gas chromatography/mass spectrometry to the identification of oriental lacquers: study of two lacquered shields - Frade, José Carlos (2015)
Oriental lacquers have been used as coating materials for thousands of years for wooden, ceramics, leather and metal objects. Lacquers are natural polymers obtained from three species growing in different regions of Asia: Rhus vernicifera (China, Japan and Korea); Rhus succedanea (Vietnam and Taiwan); and Melanorrhoea usitate (Myanmar and Thailand). The identification of lacquer films is important for conservation and restoration purposes, as well as for art history studies because it may help in determining the origin of the lacquered objects. In this work, pyrolysis-gas chromatography/mass spectrometry using a filament-type pyrolyser was successfully applied to the characterization of oriental lacquers. A method to identify the three kinds of lacquer was developed and applied to the study of two lacquered shields imported from Asia in the sixteenth century. The materials that constitute the shields were also examined by Fourier-transform infrared microspectroscopy and details of the lacquering technique are reported